2022
DOI: 10.5194/acp-22-9483-2022
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hydrogen peroxide over Europe during the BLUESKY aircraft campaign

Abstract: Abstract. In this work we present airborne in situ trace gas observations of hydrogen peroxide (H2O2) and the sum of organic hydroperoxides over Europe during the Chemistry of the Atmosphere – Field Experiments in Europe (CAFE-EU, also known as BLUESKY) aircraft campaign using a wet chemical monitoring system, the HYdrogen Peroxide and Higher Organic Peroxide (HYPHOP) monitor. The campaign took place in May–June 2020 over central and southern Europe with two additional flights dedicated to the North Atlantic f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…In particular, during five days with coordinated flights over Germany (23,26,and 28 May) and over the North Atlantic (30 May, 2 June), the payload offered the opportunity to probe the air masses in more detail. An overview of the BLUESKY mission is given in Voigt et al (2022), and further detailed studies are published by Schumann et al (2021a, b), Reifenberg et al (2022), Nussbaumer et al (2022), Hamryszczak et al (2022), andKrüger et al (2022). In the present study we will focus on the sulfur compounds in the upper troposphere and lower stratosphere.…”
Section: Bluesky Missionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, during five days with coordinated flights over Germany (23,26,and 28 May) and over the North Atlantic (30 May, 2 June), the payload offered the opportunity to probe the air masses in more detail. An overview of the BLUESKY mission is given in Voigt et al (2022), and further detailed studies are published by Schumann et al (2021a, b), Reifenberg et al (2022), Nussbaumer et al (2022), Hamryszczak et al (2022), andKrüger et al (2022). In the present study we will focus on the sulfur compounds in the upper troposphere and lower stratosphere.…”
Section: Bluesky Missionmentioning
confidence: 99%
“…5g/h). Additionally, Hamryszczak et al (2022) found that hydrogen peroxides were scavenged by clouds during BLUESKY in the lower and middle troposphere (0-7 km). As SO 2 can easily be scavenged by clouds (Seinfeld and Pandis, 2006), the potential for SO 2 being transported from the local PBL to the UT seems unlikely.…”
Section: Stratospherically and Tropospherically Influenced Air Massesmentioning
confidence: 99%
“…Hydroperoxides were measured as the sum of organic hydroperoxides and hydrogen peroxide and were determined using a wet chemical system named the Hydrogen Peroxide and Higher Organic Peroxides monitor (HYPHOP; (Klippel et al, 2011;Bozem et al, 2017;Hottmann et al, 2020;Hamryszczak et al, 2022) based on a previous design by Lazrus et al Lazrus et al, 1986). The ambient air was sampled from the top of the aircraft fuselage via a trace gas inlet (TGI) with a ½" PFA liner that left the cabin again through a second exhaust line.…”
Section: Hydrogen Peroxide Measurementsmentioning
confidence: 99%
“…Please note that the steadystate calculations, which are based on observed levels of OH, HO2, and H2O2 photolysis rates, only account for photochemical production and loss of hydrogen peroxide. EMAC simulations additionally account for vertical and horizontal transport processes, as well as local losses due to cloud scavenging (Hamryszczak et al, 2022). Thus, deviations between local photostationary steady-state budget calculations and EMAC simulations can be used to identify and quantify the impact of convective processes in the ITCZ on the budget of H2O2 in the upper troposphere.…”
Section: Comparison Of Measured Hydrogen Peroxide With Photostationar...mentioning
confidence: 99%
“…More re-Z. Hamryszczak et al: HYPHOP: H 2 O 2 and ROOH monitor cent studies on the hydroperoxides have provided insights into their tropospheric abundance and their importance in atmospheric oxidative processes (Gunz and Hoffmann, 1990;Sakugawa et al, 1990;Reeves and Penkett, 2003;Klippel et al, 2011;Fischer et al, 2019;Hottmann et al, 2020;Allen et al, 2022a, b;Hamryszczak et al, 2022;Dienhart et al, 2023;Hamryszczak et al, 2023). Thus, it is not surprising that over the past decades, numerous hydroperoxide measurement methods have been established to investigate the species in both the gaseous and aqueous phases of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%